Roma borçlar hukukunda hata - Büyükay, Yusuf (My University, 2001)
There is not general criterium to determine errors which causes annullament of contract in Roman Law. That is, Corpus Iuris Civilis haven't give us any general formula for determining the essential errors . In Roman Law, only for some error types are essential errors, but other error types haven't considered. This is a result of casuistic tradition of Roman Law. As a result of that, sorts of essential errors are determined numerus clausus. According to these classificaition, error in negotio, error in corpore, error in persona, error in pretio, error in substantia are essential errors. Even there is difference opinions between Roman lawyers, validity and time of the rule of Errantis voluntas nulla est is an interpretation rule in classic and post-classic times, which is used only in unilateral transactions.and without form transactions. The person who suffered by error has not a possibility for lawsuit, actio de errore. Instead of it, he could use rei vindicatio, condictio indebiti, actiones aedelicia, exceptio doli, in integrum restitutio lawsuits. In Roman law, either in classic or post classic times, provisions of error and responsibility from defect can't competite to each other.
Keywords: Borçlar Hukuku; Borçlu ve alacaklı; Hukuk; Hukuk_Borçlar Hukuku; Özel hukuk; Ticaret hukuku